2018
DOI: 10.1080/08820139.2018.1467925
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA-G 14bp Gene Polymorphism and Serum sHLA-G Protein Concentrations in Preeclamptic Patients and Normal Pregnant Women

Abstract: Our results demonstrate that measurement of sHLA-G protein level may be helpful as a primary diagnosis for the pathogenesis of PE. Overall, this study suggests that the association between HLA-G 14 bp polymorphism and serum sHLA-G level in different ethnic populations of PE should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…Hylenius et al reported that paternal inheritance of a 14-bp deletion/insertion in HLA-G can be important for PE onset 13 . However, several follow-up studies failed to support the findings of Hylenius et al [14][15][16][17] . Among those studies, Larsen et al found that the 14-bp deletion/insertion polymorphism (rs371194629) accompanying other polymorphisms in exon 8 (rs1710, rs1063320, rs9380142, and rs1610696) was associated with PE in the primipara when the fetus was homozygous for the insertion 18 .…”
mentioning
confidence: 90%
“…Hylenius et al reported that paternal inheritance of a 14-bp deletion/insertion in HLA-G can be important for PE onset 13 . However, several follow-up studies failed to support the findings of Hylenius et al [14][15][16][17] . Among those studies, Larsen et al found that the 14-bp deletion/insertion polymorphism (rs371194629) accompanying other polymorphisms in exon 8 (rs1710, rs1063320, rs9380142, and rs1610696) was associated with PE in the primipara when the fetus was homozygous for the insertion 18 .…”
mentioning
confidence: 90%
“…Soluble HLA-G has been detected in plasma or serum not only from pregnant women but also from nonpregnant ones; however, the concentration of sHLA-G was higher in blood from pregnant than that from non-pregnant women. In addition, sHLA-G levels were higher in the first trimester of pregnancy compared to the second and third trimesters (19), while low levels of sHLA-G have been detected in recurrent miscarriage (20), miscarriage in IVF pregnancies (21), as well as preeclampsia (22). In addition, HLA-G as an important mediator of immune escape has been also described in other immunemediated disorders, malignancies, and transplantation (23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 97%
“…Maternal serum with higher levels of sHLA-G has been identified in females with successful pregnancy when compared with pre-eclampsia patients [24]. Lower sHLA-G levels in the maternal blood, with down regulated HLA-G and decreased proportion of HLA-G+ cells have been identified in patients with preeclampsia and are thought to be are strongly associated with preeclampsia [24][25][26]. The 14 bp ins/del in the 3′UTR of region exon 8 have been extensively studied, and it has been reported to be related to severe pre-eclampsia [15].…”
Section: Hla-g and Pregnancy Disordersmentioning
confidence: 99%
“…The 14 bp ins/del in the 3′UTR of region exon 8 have been extensively studied, and it has been reported to be related to severe pre-eclampsia [15]. But on the contrary, there are studies which have reported no significant association of the 14 bp polymorphism with preeclampsia [24][25][26] implicating that differences in the ethnic population should be considered for the association between HLA-G 14 bp polymorphism and serum sHLA-G level. The SNP at position +3172 (G/A) leading to decreased in mRNA stability has been linked to pre-eclampsia [19].…”
Section: Hla-g and Pregnancy Disordersmentioning
confidence: 99%